Concentrations of connective tissue growth factor in patients with nonalcoholic fatty liver disease: Association with liver fibrosis - (:unkn) unknown (Hindawi Limited, 2012)
Aim: In this study, we aimed to investigate the relationship between the histological fibrosis stage of nonalcoholic fatty liver disease (NAFLD) and serum connective tissue growth factor (CTGF) to determine the usefulness of this relationship in clinical practice. Methods: Serum samples were collected from 51 patients with biopsy-proven NAFLD and 28 healthy controls, and serum levels of CTGF were assayed by ELISA. Results: Levels of CTGF were significantly higher in patients with NAFLD compared with controls (P=0.001). The serum CTGF levels were significantly increased, that correlated with histological fibrosis stage, in patients with NAFLD [in patients with no fibrosis (stage 0) 308.2 ± 142.9, with mild fibrosis (stage 1-2) 519.9 ± 375.2 and with advanced fibrosis (stage 3-4) 1353.2 ± 610 ng/l, P < 0.001]. Also serum level of CTGF was found as an independent predictor of histological fibrosis stage in patients with NAFLD (β = 0.662, t=5.6, P <0.001). The area under the ROC curve was estimated 0.931 to separate patients with severe fibrosis from patients with other fibrotic stages. Conclusion: Serum levels of CTGF may be a clinical utility for distinguishing NAFLD patients with and without advanced fibrosis. © 2012 - IOS Press and the authors. All rights reserved.
Keywords: connective tissue growth factor (CTGF); fibrosis; Nonalcoholic fatty liver disease (NAFLD); nonalcoholic steatohepatitis (NASH)